(untitled) (Malaysian Management Journal, 2021)
This study investigated the competitiveness index of the fourteen states in Malaysia. It also examined various aspects of competitiveness among states and vital elements that might influence competitiveness by utilizing a three-level hierarchical indicator system encompassing economic, social and environmental factors. An equally weighted index was applied to scrutinize the three dimensions. The index output was based on 24 indicators across six components. The critical components were economic performance, economic structure, marketization and openness, social aspects, domestic security and environmental quality. This study also examined the relationship between the components of competitiveness and economic growth for states in Malaysia by using the panel data estimation approach; a method which utilised data sets for fourteen states over a period extending from 2005 to 2016. Data were then analysed using a panel data regression model. Overall, findings showed that Selangor, where Kuala Lumpur the national capital was situated, was the most competitive state. In 2016, Kuala Lumpur was the best performer in terms of economic performance, social aspects and environmental quality. It was also found that domestic security and environmental quality were significant determinants of economic growth, which had enhanced competitiveness among states in Malaysia. A state’s performance according to the three dimensions varied greatly as there were different factors of specializations for each state. This study has proposed that each state in the federation possessed a significant economic performance, as well as substantial social and environmental development to ensure and sustain their respective state of competitiveness.